Aktivitas Penghentian Pendarahan Luar Ekstrak Etanol Daun Berenuk (Crescentia cujete L) Secara In-Vivo - Kusuma, Anjar Mahardian; Sulistyo, Adri Nurrakhmat; Susanti, Susanti; Sabikis, Sabikis (UI Scholars Hub, 2014)
Crescenti cujete L. or better known as calabash is a plant that thrives in Indonesia. Calabash has a great potential as an herbal remedy, but there is only some scientific research conducted on this plant, one of which is antibacterial against Bacillus subtilis and Escerichia coli on 2006 by Susanti. The method in this research was an experimental activities of the cessation external bleeding with 3 dose variation of calabash leaf extract 80%, 60%, and 40% by counting the bleeding time at base of the tail in mice. As a result, all groups of external bleeding cessation activities have better outcomes than negative controls (p < 0,05).